Thermoplastic film using recycled resin composition and production method, and barrier multilayer film for recycling

The thermoplastic film addresses the barrier and odor issues in existing regeneration technologies by using a recycled resin composition with a specific barrier layer thickness and minimal compatibilizing materials, achieving effective barrier performance and odor reduction.

JP2025056974APending Publication Date: 2025-04-09UBE FILM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023166551
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing barrier multilayer films for regeneration face issues with insufficient barrier performance and odor problems, as seen in Patent Documents 1 and 2.

Method used

A thermoplastic film with a recycled layer containing a specific ratio of thermoplastic resin and recycled resin composition from a barrier multilayer film, where the barrier layer has a thickness ratio of 6% to 32% and is unstretched, minimizing the use of compatibilizing materials in the outermost surface layers.

Benefits of technology

The solution provides a thermoplastic recycled film with improved barrier performance, reduced odor, and enhanced recyclability, resulting in a film with good appearance and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056974000001_ABST
    Figure 2025056974000001_ABST
Patent Text Reader

Abstract

To provide a barrier multilayer film for recycling which has low odor and sufficient barrier performance, and a thermoplastic recycled film using the same.SOLUTION: A thermoplastic film has a recycled layer containing 0 to 90 pts.wt. of a thermoplastic resin, and 10 to 100 pts.wt. of a recycled resin composition, wherein the recycled resin composition is a recycled article of a barrier multilayer film having an unstretched barrier layer, a thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less, and the barrier multilayer film does not substantially contain a compatibilizing material in a layer constituting its outermost surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic film using a recycled resin composition, a production method thereof, and a barrier multilayer film for recycling. [Background technology]

[0002] Conventionally, attempts have been made to use recycled packaging materials made of multilayer films having a barrier layer by remelting the packaging materials.

[0003] Patent Document 1 proposes a recyclable barrier film comprising a first layer containing high-density polyethylene and a barrier layer containing a polymer other than polyethylene, the polymer acting to reduce oxygen permeability through the barrier film compared to the oxygen permeability through the first layer, and the barrier layer being present in the barrier film in an amount of less than 5 weight percent based on the total weight of the barrier film.

[0004] Patent Document 2 describes a recyclable laminate having at least a sealant layer and a reinforcing layer, which does not contain one or more selected from the group consisting of metal foil, metal vapor deposition film, and metal oxide vapor deposition film, the sealant layer 3 contains linear low-density polyethylene and a compatibilizer, the content of the compatibilizer in the entire sealant layer is 5 to 20 weight %, the reinforcing layer contains ethylene-vinyl alcohol copolymer (EVOH) or polyamide resin, and the thickness of the reinforcing layer is 5 to 20% of the entire thickness. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2017-518205 [Patent Document 2] JP 2020-11415 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the applicant found that the technology of Patent Document 1 does not provide sufficient barrier performance in a barrier multilayer film for recycling, and the applicant found that the technology of Patent Document 2 causes an odor problem in a barrier multilayer film for recycling.

[0007] In view of the above-mentioned problems in the conventional art, an object of the present invention is to provide a recycled barrier multilayer film having low odor and sufficient barrier performance, and a thermoplastic recycled film using the same. [Means for solving the problem]

[0008] The present invention is a thermoplastic film having a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of a recycled resin composition, The recycled resin composition is a recycled product of a barrier multilayer film having an unstretched barrier layer, the thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; The present invention provides a thermoplastic film, the outermost layer of which is substantially free of a compatibilizer.

[0009] The present invention also provides a method for producing a thermoplastic film having a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of a recycled resin composition, The recycled resin composition is a recycled product of a barrier multilayer film having an unstretched barrier layer, the thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; The present invention provides a method for producing a thermoplastic film, wherein the barrier multilayer film is substantially free of a compatibilizer in a layer constituting the outermost surface thereof.

[0010] The present invention also provides a regenerated barrier multilayer film having an unstretched barrier layer and being recycled as a thermoplastic film, comprising: the thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; The present invention provides a barrier multilayer film, the outermost layer of which is substantially free of a compatibilizing agent. Effect of the Invention

[0011] The present invention can provide a thermoplastic recycled film with good appearance by using a recycled barrier multilayer film with low odor and sufficient barrier performance. The present invention also provides a recycled barrier multilayer film with low odor, sufficient barrier performance, and high recyclability. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the layer structure of the barrier multilayer film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The thermoplastic film of the present invention will be described in detail below based on a preferred embodiment. A specific example will be shown, but the present invention is not limited thereto. The upper and lower limits described below can be combined in any combination without any restrictions.

[0014] The thermoplastic film of the present invention has a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of a recycled resin composition. The recycled resin composition is a recycled product of a barrier multilayer film having an unstretched barrier layer. First, the barrier multilayer film having an unstretched barrier layer will be described.

[0015] [Barrier multi-layer film] The barrier multilayer film of the present invention (sometimes referred to as a "barrier multilayer film") has at least an unstretched barrier layer and has a plurality of layers.

[0016] [Barrier layer] The barrier layer is a layer having gas barrier properties. The barrier layer preferably contains at least one selected from the group consisting of polyamide and ethylene-vinyl alcohol copolymer (EVOH). The barrier layer preferably contains at least one selected from the group consisting of polyamide and ethylene-vinyl alcohol copolymer (EVOH) as a main constituent resin. For example, at least one selected from the group consisting of polyamide and ethylene-vinyl alcohol copolymer (EVOH) accounts for preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more of the barrier layer.

[0017] The polyamide is obtained by polymerizing or copolymerizing a raw material such as lactam, aminocarboxylic acid, or nylon salt of diamine and dicarboxylic acid by a known method such as melt polymerization, solution polymerization, or solid-phase polymerization. Specific examples of polyamides used in the present invention include polycaprolactam (polyamide 6), polyundecane lactam (polyamide 11), polydodecane lactam (polyamide 12), polyhexamethylene adipamide (polyamide 66), polyhexamethylene azelamide (polyamide 69), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene undecamide (polyamide 611), polyhexamethylene dodecamide (polyamide 612), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polymetaxylylene adipamide (polyamide MXD6), and polyamide copolymers using these raw material monomers. These can be used alone or in combination. Preferred examples include nylon 6 and nylon 6 / 66 copolymers.

[0018] Examples of the ethylene-vinyl alcohol copolymer (EVOH) include resins obtained by copolymerizing ethylene with a vinyl ester monomer, saponifying the resulting copolymer, and converting the vinyl ester unit into a vinyl alcohol unit. Examples of the vinyl ester monomer include vinyl carboxylates such as vinyl formate, vinyl acetate, vinyl butyrate, and vinyl benzoate. The greater the proportion of vinyl alcohol units in EVOH, the more improved the barrier properties are, but the lower the moisture resistance is. Therefore, it is preferable that EVOH has an appropriate ethylene content. From the viewpoint of gas barrier properties, the ethylene content of the ethylene-vinyl alcohol copolymer (EVOH) is preferably, for example, 20 to 60 mol%, and more preferably 25 to 50 mol%. The degree of saponification of the ethylene-vinyl alcohol copolymer (EVOH) is not limited to 100 mol%, but is preferably, for example, 80 mol% or more.

[0019] The melting point of the barrier layer is preferably 230°C or lower, and more preferably 135°C or higher and 220°C or lower, from the viewpoint of enhancing the barrier properties of the barrier multilayer film, suppressing poor appearance due to gelation when recycled by melt kneading, and making it easy to obtain a thermoplastic film with high transparency and high strength. In particular, from the above viewpoints, when the barrier layer contains an ethylene-vinyl alcohol copolymer (EVOH), the melting point of the EVOH is preferably 210°C or lower, more preferably 150°C or higher and 210°C or lower, and even more preferably 155°C or higher and 200°C or lower. Furthermore, when the barrier layer contains nylon, the melting point of nylon is preferably 230° C. or less, more preferably 1150° C. or more and 225° C. or less, and further preferably 180° C. or more and 220° C. or less. The melting point can be measured in accordance with JIS K7121. It is also preferable that the melting point of the barrier layer is within the above range.

[0020] When the barrier layer contains an ethylene-vinyl alcohol copolymer (EVOH), the MFR of the EVOH is preferably 0.3 g / 10 min to 15 g / 10 min, more preferably 0.5 g / 10 min to 10 g / 10 min, and even more preferably 1 g / 10 min to 8 g / 10 min, in terms of film-forming and processability. The MFR of the ethylene-vinyl alcohol copolymer (EVOH) is measured by Method A in accordance with JIS K7210:1999, under conditions of a temperature of 190°C and a load of 2.16 kg.

[0021] The density of the barrier layer is preferably 1.0 g / cm from the viewpoint of improving the barrier property. 3 More preferably, 1.05 g / cm 3 More than 1.3g / cm 3 More preferably, 1.10 g / cm or less. 3 More than 1.25g / cm 3 It is also preferable that the density of the EVOH or nylon constituting the barrier layer is within the above range.

[0022] The thickness ratio of the barrier layer is preferably 6% or more and 32% or less with respect to the total thickness of the barrier multilayer film. By making the thickness of the barrier layer 6% or more with respect to the total thickness of the barrier multilayer film, the barrier properties of the barrier multilayer film are less likely to decrease, and the tensile strength of the film is less likely to decrease. Furthermore, by making the thickness of the barrier layer 32% or less with respect to the total thickness of the barrier multilayer film, the rigidity of the barrier multilayer film is prevented from becoming too high, and it becomes possible to obtain homogeneity and transparency when remelted. From these points of view, the thickness ratio of the barrier layer is particularly preferably 6.5% or more and 30% or less, and particularly preferably 7.5% or more and 29% or less with respect to the total thickness of the barrier multilayer film. In particular, when the barrier layer is made of an ethylene-vinyl alcohol copolymer (EVOH), the thickness ratio of the barrier layer to the total thickness of the barrier multilayer film is preferably 6% or more and 25% or less, more preferably 6.5% or more and 20% or less, and even more preferably 7.5% or more and 17% or less. When the barrier layer is made of polyamide, the thickness ratio of the barrier layer to the total thickness of the barrier multilayer film is preferably 10% to 32%, more preferably 15% to 30%, and even more preferably 20% to 29%.

[0023] The barrier multilayer film may have one or more barrier layers, or may have multiple layers. An example of a barrier multilayer film having multiple barrier layers is one having an ethylene-vinyl alcohol copolymer (EVOH) layer and a polyamide layer. When there are multiple barrier layers, the thickness ratio of the barrier layers refers to the ratio of the total thickness of the multiple barrier layers.

[0024] In the barrier layers described above, polyolefin resins modified with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, and the like, terpolymer resins of ethylene-(meth)acrylic acid ester-unsaturated carboxylic acid, cyclic polyolefin resins, cyclic olefin copolymers, polyethylene terephthalate (PET), polyacrylonitrile (PAN), and the like may be used in appropriate amounts within the range that does not impair the odor suppression effect.

[0025] In the multilayer barrier film used in the present invention, the barrier layer is an unstretched layer, which is preferable because it is easy to configure the multilayer barrier film of the present invention to have good barrier performance, tensile strength and shape stability. In the present invention, it is preferable that the barrier multilayer film itself is unstretched, since this makes it easier to configure the barrier multilayer film to have better barrier properties, tensile strength and shape stability. An example of an unstretched barrier multilayer film is a film that is not stretched after multilayer extrusion by inflation.

[0026] A barrier multilayer film 10 shown in Fig. 1 is an example of a barrier multilayer film used in the present invention. The barrier multilayer film 10 has a first layer 1 constituting the outermost surface on one of its two sides, and a second layer 2 constituting the outermost surface on the other side. These layers have higher oxygen permeability than the barrier layer. In this specification, the layer constituting the outermost surface of the barrier multilayer film is also referred to as the "outermost layer".

[0027] Of the first layer 1 and the second layer 2, at least one (the innermost layer of the package) preferably corresponds to a sealant layer. The sealant layer preferably contains a thermoplastic resin as a heat-sealable resin. Examples of the thermoplastic resin include polyolefin resins such as polyethylene (PE), low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), metallocene polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl (meth)acrylate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-propylene copolymer, and methylpentene polymer. Among these, from the viewpoints of excellent heat-sealability, economic efficiency, odor prevention, and moldability, the sealant layer preferably contains a polyethylene-based resin or a polypropylene-based resin as a heat-sealable resin, more preferably a polyethylene-based resin, and particularly preferably low-density polyethylene (LDPE) or linear low-density polyethylene (LLDPE). A polyolefin resin refers to a polymer containing 50% by weight or more of structural units derived from olefin, preferably more than 60% by weight. A polyethylene resin refers to a polymer containing 50% by weight or more of structural units derived from ethylene, preferably more than 60% by weight. A polypropylene resin refers to a polymer containing 50% by weight or more of structural units derived from propylene, preferably more than 60% by weight. The proportion of the polyethylene resin or polypropylene resin in the sealant layer is preferably 50% by weight or more, more preferably 60% by weight or more, particularly preferably 70% by weight or more, even more preferably 80% by weight or more, and most preferably 90% by weight or more. The sealant layer is preferably a layer laminated by coextrusion from the viewpoint of reducing the number of work steps and from the viewpoint of economy. In particular, it is preferable that the content of the polyethylene resin is equal to or more than the lower limit.

[0028] Furthermore, in the present invention, it is preferable that both the first layer 1 and the second layer 2 are mainly composed of a thermoplastic resin. This composition is preferable in terms of the transparency and homogeneity of the recycled thermoplastic film and the moldability. In this case, the thermoplastic resin used for the other outermost layer (the outermost layer in the package) of the first layer 1 and the second layer 2 can be the same as the resin listed above as the constituent resin of the sealant layer. Therefore, the composition listed above as the composition of the sealant layer can be applied to both the first layer 1 and the second layer 2 without any restrictions. In particular, the first layer 1 and the second layer 2 preferably contain a polyethylene-based resin or a polypropylene-based resin in terms of the transparency and homogeneity of the recycled thermoplastic film and the moldability, and more preferably contain a polyethylene-based resin, and particularly preferably contain a low-density polyethylene (LDPE) or a linear low-density polyethylene (LLDPE). The proportion of the polyethylene resin or polypropylene resin in the outermost layer is preferably 50% by weight or more, more preferably 60% by weight or more, particularly preferably 70% by weight or more, further preferably 80% by weight or more, and most preferably 90% by weight or more. In particular, it is preferable that the content of the polyethylene resin is equal to or more than the lower limit.

[0029] The first layer 1 and the second layer 2 do not substantially contain a compatibilizer. The compatibilizer is a carboxylic acid-modified polyolefin, which is a component that improves the compatibility of the molten mixture when the barrier multilayer film 10 is melt-kneaded, and has the effect of homogenizing and clarifying the mixture. Specifically, maleic anhydride olefin is included, and more specifically, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene (block or random) copolymer, maleic anhydride-modified ethylene-ethyl acrylate copolymer, and maleic anhydride-modified ethylene-vinyl acetate copolymer are included. "Substantially not containing a compatibilizer" means that the content of the compatibilizer in each of the first layer 1 and the second layer 2 is less than 1% by weight, preferably 0.5% by weight or less, more preferably 0.1% by weight or less, and most preferably no compatibilizer is included. By configuring in this way, the barrier multilayer film 10 can be obtained in which the unique odor of the compatibilizer is effectively reduced.

[0030] In order to enhance recyclability as a highly compatible mixture, when a thermoplastic resin is used in the first layer 1 and / or the second layer 2, the melting point of the thermoplastic resin is preferably 80° C. or higher, more preferably 85° C. or higher, and particularly preferably 90° C. or higher. The melting point is preferably 180° C. or lower, more preferably 170° C. or lower, even more preferably 140° C. or lower, particularly preferably 135° C. or lower, and most preferably 130° C. or lower. It is also preferable that the melting point of the first layer 1 and / or the second layer 2 is within the above range.

[0031] From the viewpoint of enhancing recyclability as a highly compatible mixture, when a thermoplastic resin is used in the first layer 1 and / or the second layer 2, the MFR of the thermoplastic resin is preferably 0.1 g / 10 min to 50 g / 10 min, more preferably 0.3 g / 10 min to 40 g / 10 min, and particularly preferably 0.4 g / 10 min to 30 g / 10 min. The MFR of the thermoplastic resin used in the first layer 1 and / or the second layer 2 can be measured under a load of 2.16 kg at 190°C.

[0032] In order to increase the mechanical strength of the barrier multilayer film or the thermoplastic film, when a thermoplastic resin is used in the first layer 1 and / or the second layer 2, the density of the thermoplastic resin is 0.860 g / cm 3 More than 0.870 g / cm is preferable. 3 More preferably, 0.880 g / cm 3 More preferably, 0.890 g / cm 3 More preferably, 0.895 g / cm 3 Above this level is particularly preferred, with 0.900 g / cm 3 The density of the thermoplastic resin is most preferably 0.970 g / cm. 3 Less than 0.965 g / cm is preferred. 3 Less than 0.960 g / cm is more preferable. 3 The following are particularly preferred: It is also preferred that the density of the first layer 1 and / or the second layer 2 is within the above ranges.

[0033] The thickness of each of the first layer 1 and the second layer 2 is preferably 10% or more of the thickness of the barrier multilayer film 10 from the viewpoint of molding processability, more preferably 15 to 49%, and particularly preferably 20 to 45%.

[0034] 1, the first layer 1 and the second layer 2 are disposed opposite both sides of the barrier layer 3. As a typical example, the barrier layer 3 is disposed in a state sandwiched between the inner surfaces of the first layer 1 and the second layer 2, via adhesive layers 4, 4 that are in direct contact with the barrier layer 3 on both sides.

[0035] The adhesive component used in the adhesive layers 4, 4 is preferably an acid-modified polyolefin. Examples of the acid-modified polyolefin include those listed above as examples of the compatibilizer. In the present invention, it is particularly preferable to use maleic anhydride-modified polyethylene as the adhesive component used in the adhesive layers 4, 4, and it is particularly preferable to use maleic anhydride-modified low-density polyethylene. These adhesive components enhance the adhesion between the barrier layer and the olefin layer, and as described above, when the barrier multilayer film is melt-kneaded, they improve the compatibility of the molten mixture, thereby achieving the effects of homogenization and transparency.

[0036] In the present invention, it is preferable that the adhesive layer 4 located on at least one side of the barrier layer 3 contains an adhesive made of an acid-modified polyolefin, and it is particularly preferable from the viewpoint of improving the compatibility of the molten mixture that the adhesive layer 4, 4, which is a total of two or more adhesive layers 4, 4 located on both sides of the barrier layer 3, contain an adhesive made of an acid-modified polyolefin. With this configuration, it is possible to effectively improve the compatibility of the molten mixture while suppressing the odor of the barrier multilayer film, and to achieve homogeneity and transparency of the obtained thermoplastic film.

[0037] In the present invention, the amount of acid modification in the acid-modified polyolefin used in the adhesive layers 4, 4 is preferably 0.01 to 5 wt%, more preferably 0.05 to 4 wt%, and even more preferably 0.1 to 3 wt%. The amount of acid modification referred to here is the weight ratio of anhydride or carboxylic acid moieties in the acid-modified polyolefin to the acid-modified polyolefin.

[0038] In terms of the ease of improving the compatibility of the molten mixture and the moldability, the melting point of the acid-modified polyolefin is preferably 80° C. or more and 140° C. or less, more preferably 85° C. or more and 135° C. or less, and particularly preferably 90° C. or more and 130° C. or less. It is also preferable that the melting points of the adhesive layers 4, 4 are within the above range.

[0039] From the viewpoints of easily improving the compatibility of the molten mixture and of moldability, the MFR of the acid-modified polyolefin is preferably 0.3 g / 10 min to 20 g / 10 min, more preferably 0.5 g / 10 min to 15 g / 10 min, and even more preferably 0.8 g / 10 min to 10 g / 10 min. This MFR is a value measured under a load of 2.16 kg at 190°C.

[0040] In terms of the ease of mixing with the barrier layer and the mechanical strength, the density of the acid-modified polyolefin is preferably 0.860 g / cm. 3 More than 0.960g / cm 3 Less than or equal to 0.870 g / cm 3 More than 0.950g / cm 3 More preferably, 0.880 g / cm 3 More than 0.940g / cm 3 It is also preferable that the density of the adhesive layers 4, 4 is within the above range.

[0041] In the adhesive layers 4, 4, the proportion of acid-modified polyolefin is preferably 60% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, particularly preferably 90% by weight or more, and most preferably 95% by weight or more.

[0042] The thickness ratio of the adhesive layers 4, 4 is preferably 5% or more in the barrier multilayer film 10, because the effect of compatibility during melt-kneading is easily exhibited in the obtained thermoplastic film, and homogenization and transparency are good. The thickness ratio of the adhesive layers 4, 4 is preferably 30% or less in the barrier multilayer film 10, because it is possible to suppress the odor of the obtained thermoplastic film without adding a relatively large amount of thermoplastic resin in addition to the recycled resin composition in the recycling step described below, in addition to the effect of suppressing odor and maintaining strength of the barrier multilayer film 10, and is excellent in terms of economy. From this viewpoint, the thickness ratio of the adhesive layers 4, 4 is more preferably 6% or more and 25% or less, and particularly preferably 7% or more and 20% or less in the barrier multilayer film 10. When there are multiple adhesive layers, the thickness ratio of the adhesive layers 4, 4 refers to the ratio of the total thickness of the adhesive layers to the total thickness of the barrier multilayer film 10. If the thickness ratio of the adhesive layer is lower than the above range, the compatibilizing effect during melt-kneading in the recycling process is difficult to achieve, and the strength of the thermoplastic film is likely to decrease. If the thickness ratio is higher than the above range, the odor will be strong, reducing the commercial value.

[0043] 1 has five layers, including a first layer 1 and a second layer 2 constituting the outermost surface, a barrier layer 3 located inside them, and adhesive layers 4, 4 located between the first layer 1 and the second layer 2, respectively, and the barrier layer 3, and bonding the first layer 1 and the second layer 2, respectively, to the barrier layer 3. Having at least these five layers is preferable for the barrier multilayer film 10, because it allows the barrier multilayer film 10 to have good barrier properties with suppressed odor and high strength, while making it easy to form a thermoplastic film (recycled layer) obtained by recycling the barrier multilayer film 10 that is transparent, homogeneous, has a certain strength, and has suppressed odor.

[0044] The barrier multilayer film 10 may adopt a form other than that shown in FIG. 1. For example, as described above, at least one of the first layer 1 and the second layer 2 is a sealant layer, and the sealant layer may be one layer or two layers laminated. In the case of two or more layers, the layers may be of the same composition or different compositions. In the example of FIG. 1, the first layer 1 and the second layer 2 are laminated in direct contact with the adhesive layers 4, 4, but, differently, the first layer 1 and the second layer 2 may be laminated between the adhesive layers 4, 4 via a reinforcing layer. When a reinforcing layer is provided, the first layer 1 and the second layer 2 may be provided so as to be in direct contact with the reinforcing layer, or may be laminated via another layer such as an adhesive layer. Note that a second reinforcing layer may be formed between the adhesive layers 4, 4 and the barrier layer 3, but it is preferable that the adhesive layers 4, 4 and the barrier layer 3 are in direct contact with each other in terms of facilitating the production of a transparent and homogeneous thermoplastic film. The resin composition in these reinforcing layers may contain, for example, the above-mentioned thermoplastic resin and the above-mentioned compatibilizer. The barrier multilayer film 10 preferably has 5 to 11 layers, more preferably 5 to 9 layers, and particularly preferably 5 to 7 layers.

[0045] Each layer may contain, as necessary, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments for the purpose of improving and modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, antioxidant properties, slipperiness, mold releasability, flame retardancy, antifungal properties, electrical properties, strength, etc., and the amount of each additive may be arbitrarily added depending on the purpose within a range that does not adversely affect other properties. In particular, it is preferable to appropriately add lubricants and antiblocking agents to the first layer 1 and the second layer 2 in order to impart processability during film formation and packaging suitability for filling machines.

[0046] Furthermore, in order to improve adhesion, the surfaces of the films constituting the barrier multilayer film or the thermoplastic film described below may be subjected to physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas or nitrogen gas, or glow discharge treatment, or chemical treatments such as oxidation treatment using chemicals, before lamination. Such treatments are not counted in the number of layers.

[0047] It is preferable that the barrier multilayer film does not contain a metal foil, a metal vapor deposition film or a metal oxide vapor deposition film in terms of the transparency and homogeneity of the recycled resin composition obtained from the barrier multilayer film.

[0048] The thickness of the barrier multilayer film 10 is, for example, preferably 10 to 250 μm, and more preferably 20 to 200 μm.

[0049] [Recycled resin composition] The recycled resin composition used in the present invention is preferably obtained by melt-kneading the barrier multilayer film. The recycled resin composition can be produced by pulverizing a composition of the barrier multilayer film or its scraps, and using a commonly used resin kneading device, pelletizing device, or moisture removing device. For example, examples of the kneading device include a single screw extruder, a twin screw extruder, a multi-screw extruder, a Banbury mixer, a pressure kneader, a rotating roll, and an internal mixer. The kneading is performed by melt kneading at a temperature equal to or higher than the melting point of the resin used. The temperature of the melt kneading is preferably 210 to 250°C, more preferably 220 to 240°C, and particularly preferably 225 to 235°C. By setting the temperature within this range, a transparent and homogeneous thermoplastic film can be easily obtained, and there is also an advantage in that gelation by the thermoplastic resin is suppressed.

[0050] Pelletizing may be carried out using a strand cut system in which the strands extruded from the die outlet are collected, cooled, and cut; however, the present invention is not limited to this system and may also be a hot cut system or an underwater cut system. After pelletization, moisture in the pellets is removed by dehydration using a stretch separator or drying using a dryer.

[0051] In preparing the recycled resin composition, the raw materials may contain components other than the barrier multilayer film 10, but the barrier multilayer film 10 preferably accounts for 50% by weight or more of the raw materials of the recycled resin composition, more preferably accounts for 60% by weight or more, even more preferably accounts for 70% by weight or more, even more preferably accounts for 80% by weight or more, even more preferably accounts for 90% by weight or more, and particularly preferably accounts for 100% by weight. The barrier multilayer film referred to here includes remnants of the barrier multilayer film.

[0052] [Thermoplastic film] The thermoplastic film has a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of the recycled resin composition. In order to obtain a thermoplastic film having good strength, suppressed odor, and good appearance, the proportion of the thermoplastic resin in the total of the thermoplastic resin (non-recycled resin) and the recycled resin composition is preferably 10 to 90% by weight, more preferably 10 to 70% by weight. In the recycled layer, the total amount of the thermoplastic resin and the recycled resin composition is preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight.

[0053] The thermoplastic resin used in combination with the recycled resin composition is a non-recycled resin. The thermoplastic resin is preferably a polyolefin resin. Specifically, polyethylene such as high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid ester copolymer, etc. can be mentioned. Among them, it is preferable to use polyolefin, particularly polyethylene, and particularly low density polyethylene and linear low density polyethylene, from the viewpoint of obtaining a thermoplastic film having good moldability, suppressed odor, and good appearance.

[0054] In order to improve the homogeneity of the resulting recycled layer and to facilitate molding, when a thermoplastic resin is used as the non-recycled resin, the melting point of the thermoplastic resin is preferably 80°C or higher and 140°C or lower, more preferably 85°C or higher and 135°C or lower, and particularly preferably 90°C or higher and 130°C or lower.

[0055] In terms of improving the homogeneity of the resulting recycled layer and moldability, when a thermoplastic resin is used as the non-recycled resin, the MFR of the thermoplastic resin is preferably 0.3 g / 10 min to 20 g / 10 min, more preferably 0.5 g / 10 min to 15 g / 10 min, and particularly preferably 0.8 g / 10 min to 10 g / 10 min. The MFR of the thermoplastic resin as the non-recycled resin can be measured at a load of 2.16 kg and 190°C.

[0056] When using a thermoplastic resin as the non-recycled resin, in order to improve the homogeneity of the obtained recycled layer and in terms of moldability, the density of the thermoplastic resin is 0.860 g / cm 3 More than 0.960g / cm 3 Less than 0.870 g / cm is preferred. 3 More than 0.950g / cm 3 Less than 0.880 g / cm is more preferable. 3 More than 0.940g / cm 3 The following are particularly preferred:

[0057] The thermoplastic film of the present invention is a film produced using the recycled resin composition of the present invention. The thermoplastic film may be one layer or may be composed of two or more layers, provided that it contains the recycled layer. In the case of two or more layers, the layers may be of the same composition or different compositions. In addition, the layers may be laminated via an adhesive layer.

[0058] The thermoplastic film can be produced and laminated by, for example, a method of producing a film using one type of recycled resin composition and, if necessary, the above-mentioned thermoplastic resin, by a film-forming method such as an extrusion method, a cast molding method, a T-die method, a cutting method, or an inflation method; a method of producing a multilayer film by co-extrusion using two or more resins, and using the recycled resin composition and, if necessary, the above-mentioned thermoplastic resin as at least one of the resins; a method of mixing two or more recycled resins and, if necessary, the above-mentioned thermoplastic resin before film production, and producing a film by the above-mentioned film-forming method; a dry lamination method, a sand lamination method, etc., can be appropriately selected to produce a film, laminate, or simultaneously produce a film and laminate. The same method can also be used when producing a recycled film by laminating a layer or film made of a resin composition other than the recycled resin composition of the present invention.

[0059] In the recycled layer, the composition ratio obtained by multiplying the thickness ratio of the adhesive layer in the barrier multilayer film by the weight ratio of the recycled resin composition in the thermoplastic film is preferably 5% or more, in terms of making it easy to obtain a thermoplastic film with good appearance and homogeneity, and in terms of balancing the barrier performance of the original barrier multilayer film with the economically efficient use of the recycled resin composition. In the recycled layer, the composition ratio obtained by multiplying the thickness ratio of the adhesive layer in the barrier multilayer film by the weight ratio of the recycled resin composition in the thermoplastic film is preferably 20% or less, in terms of suppressing film odor. From this viewpoint, the composition ratio is preferably 6% or more and 19% or less, more preferably 7% or more and 17% or less.

[0060] In the recycled layer, the composition ratio obtained by multiplying the thickness ratio of the barrier layer in the barrier multilayer film by the weight ratio of the recycled resin composition in the thermoplastic film is preferably 30% or less in terms of high heat seal strength of the film, more preferably 25% or less, and particularly preferably 22% or less. In addition, in the recycled layer, the composition ratio obtained by multiplying the thickness ratio of the barrier layer in the barrier multilayer film by the weight ratio of the recycled resin composition in the thermoplastic film is preferably 1% or more in terms of economically efficient use of the recycled resin composition, more preferably 2% or more, and particularly preferably 3% or more.

[0061] It is desirable that the thermoplastic film produced using the recycled resin composition of the present invention is used as a recycled film that does not deteriorate the performance expected of polyolefin.

[0062] [Packaging] The thermoplastic film of the present invention can be used for various packages (sometimes called "packaging materials") for packaging, food preservation, agriculture, civil engineering, fishing, automobile interior / exterior, marine, daily necessities, building material interior / exterior, housing equipment, medical / medical equipment, pharmaceuticals, home appliances, furniture, stationery / office supplies, sales promotion, commercial, electrical / electronics industry, etc. Examples of packaging include foods such as marine products, fresh foods such as vegetables and fruits, dried foods, rice, cereals, beverages, processed foods, seasonings, spices, livestock products, snacks, health foods, and frozen foods; beverages such as pouched beverages; sanitary products and daily necessities such as detergents, soaps, air fresheners, deodorants, shampoos, rinses, hair treatments, dentifrices, bath additives, and cosmetics; pharmaceuticals and their secondary packaging, as well as daily necessities, and various packaged items, including not only solids but also liquids and mixtures thereof. EXAMPLES

[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The raw materials used in the examples are as follows. LDPE1: Ube Maruzen Polyethylene Co., Ltd., UBE Polyethylene F022NH, MFR 0.8g / 10min, density 0.922g / cm 3 , melting point 110℃. Adhesive 1: Maleic anhydride modified low-density polyethylene, manufactured by Ube Maruzen Polyethylene Co., Ltd., UBEBONDF1100, MFR4.1g / 10min, density 0.910g / cm 3 , melting point 120℃. Adhesive 2: Maleic anhydride modified low density polyethylene, manufactured by Mitsui Chemicals, Admer LF128, MFR 1.4g / 10min, density 0.924g / cm 3 , melting point 110℃. EVOH1: Ethylene-vinyl alcohol copolymer (EVOH), manufactured by Kuraray Co., Ltd., EVAL E173B, MFR 2.5g / 10min, ethylene content 44mol%, density 1.14g / cm 3 , melting point 165℃. Nylon 1: UBE nylon 5033X80, density 1.14g / cm 3 , melting point 196°C.

[0064] [Example 1] (1) Manufacturing of multi-layer barrier films A 100 μm-thick, five-layer barrier film (outer layer / adhesive layer / barrier layer / adhesive layer / inner layer) having the following layer structure was produced using a co-extrusion air-cooled inflation film forming machine. The outer and inner layers were made of LDPE1, with 3% by mass (relative to LDPE1) of antiblocking agent EAZ-10 manufactured by Prime Polymer Co., Ltd. and 3% by mass (relative to LDPE1) of lubricant Ultzex ​​SQ-3 manufactured by Mitsui Chemicals, Inc. added. Adhesive 1 was used for the adhesive layer. EVOH 1 was used for the barrier layer. The thicknesses of the layers produced were 42 / 5 / 6 / 5 / 42 (all units are μm). The oxygen gas permeability and film odor of the produced barrier multilayer film are shown in Table 1. (2) Manufacturing of thermoplastic film using recycled resin composition Next, the barrier multilayer film was placed in a recycling machine capable of melt biaxial kneading, and the barrier multilayer film was pulverized, biaxially kneaded at 230°C, pelletized, and dehydrated to obtain a recycled resin composition. The recipe using the recycled resin composition is shown in Table 1. Next, a single-layer thermoplastic film having a thickness of 50 μm was produced using the obtained recycled resin composition with a T-die film forming machine. The moldability, appearance, film odor and film seal strength of the produced thermoplastic films were evaluated by the following methods. The results are shown in Table 1.

[0065] [Example 2] A barrier multilayer film and a thermoplastic film were produced in the same manner as in Example 1, except that the thicknesses of the layers in the barrier multilayer film in Example 1 were 40 / 5 / 10 / 5 / 40 (all units are μm). The oxygen gas permeability and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor and film seal strength of the thermoplastic film are shown in Table 1.

[0066] [Example 3] A barrier multilayer film and a thermoplastic film were produced in the same manner as in Example 1, except that the thicknesses of the layers of the barrier multilayer film in Example 1 were 37 / 8 / 10 / 8 / 37 (all units are μm). The oxygen gas permeability and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor and film seal strength of the thermoplastic film are shown in Table 1.

[0067] [Comparative Example 1] A barrier multilayer film and a thermoplastic film were produced in the same manner as in Example 1, except that the thicknesses of the layers in the barrier multilayer film in Example 1 were 43.5 / 5 / 3 / 5 / 43.5 (all units are μm). The oxygen gas permeability and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor and film seal strength of the thermoplastic film are shown in Table 1.

[0068] [Comparative Example 2] (1) Manufacturing of multi-layer barrier films A barrier multilayer film was produced in the same manner as in Example 1, except that the thicknesses of the layers in the barrier multilayer film in Example 1 were 20 / 5 / 50 / 5 / 20 (all units are μm). The oxygen gas permeability and film odor of the produced barrier multilayer film are shown in Table 1. (2) Manufacturing of thermoplastic film using recycled resin composition Next, a recycled resin composition was obtained from the barrier multilayer film in the same manner as in Example 1. Then, 70% by weight of the recycled resin composition and 30% by weight of LDPE1 were dry-blended. The resulting mixture was fed to a T-die film-forming machine to produce a single-layer thermoplastic film having a thickness of 50 μm. The moldability, appearance, film odor and film seal strength of the produced thermoplastic film are shown in Table 1.

[0069] [Comparative Example 3] A monolayer film having a thickness of 100 μm was produced using an air-cooled inflation film forming machine, and the oxygen gas permeability and the film odor were evaluated. The composition of the monolayer film was the same as that of the inner layer and the outer layer of the barrier multilayer film of Example 1. The oxygen gas permeability and the film odor are shown in Table 1. In addition, LDPE1 having the same composition as the inner layer and outer layer of the barrier multilayer film of Example 1 was directly fed to a T-die film forming machine to produce a single-layer thermoplastic film having a thickness of 50 μm. The single-layer film having a thickness of 50 μm was produced, and the formability, appearance, film odor and film seal strength of the film were evaluated. The evaluation results are shown in Table 1.

[0070] [Example 4] (1) Manufacturing of multi-layer barrier films A 180 μm thick, five-layer barrier multilayer film (outer layer / adhesive layer / barrier layer / adhesive layer / inner layer) having the following layer structure was produced using a co-extrusion air-cooled inflation film forming machine. The outer and inner layers were made of LDPE1 with 3% by mass (relative to LDPE1) of antiblocking agent EAZ-10 manufactured by Prime Polymer Co., Ltd. and 3% by mass (relative to LDPE1) of lubricant Ultzex ​​SQ-3 manufactured by Mitsui Chemicals, Inc. added. Adhesive 2 was used for the adhesive layer, and Nylon 1 was used for the barrier layer. The thicknesses of the layers produced were 55 / 10 / 50 / 10 / 55 (all units are μm). The tensile strength at break (hereinafter also referred to as "tensile strength") and film odor of the produced barrier multilayer film were evaluated by the following methods and are shown in Table 2. (2) Manufacturing of thermoplastic film using recycled resin composition Next, as a recycling process, the barrier multilayer film was placed in a recycling machine capable of melt biaxial kneading, and was crushed, biaxially kneaded at 230°C, pelletized, and dehydrated to obtain a recycled resin composition. The recipe using the recycled resin composition is shown in Table 2. Next, the recycled resin composition was subjected to an air-cooled inflation film forming machine to produce a single-layer thermoplastic film having a thickness of 50 μm. The moldability, appearance, film odor, and heat seal strength of the produced thermoplastic film are shown in Table 2.

[0071] [Example 5] In Example 4 (2), 70% by weight of the recycled resin composition and 30% by weight of LDPE1 were dry blended. This mixture was used instead of 100% by weight of the recycled resin composition to produce a single-layer thermoplastic film having a thickness of 50 μm. Except for this, a single-layer thermoplastic film having a thickness of 50 μm was produced in the same manner as in Example 4. The tensile strength and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor, and heat seal strength of the film are shown in Table 2.

[0072] [Example 6] In Example 4(1), the thicknesses of the layers of the barrier multilayer film were 40 / 25 / 50 / 25 / 40 (all units are μm). In Example 4(2), 50% by weight of the recycled resin composition and 50% by weight of LDPE1 were dry-blended. This mixture was used instead of 100% by weight of the recycled resin composition to produce a single-layer thermoplastic film having a thickness of 50 μm. Except for these points, a barrier multilayer film and a thermoplastic film were produced in the same manner as in Example 4. The tensile strength and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor and heat seal strength of the thermoplastic film are shown in Table 2.

[0073] [Comparative Example 4] The LDPE1 used in the outer and inner layers of the barrier multilayer film of Example 4 was changed to a mixture obtained by dry blending 85.5% by weight of LDPE1 and 14.5% by weight of adhesive 1. Except for this, a barrier multilayer film and a thermoplastic film were produced in the same manner as in Example 4. The tensile strength and film odor of the produced barrier multilayer film, as well as the moldability, appearance, film odor and heat seal strength of the thermoplastic film are shown in Table 2.

[0074] [Comparative Example 5] A monolayer film having a thickness of 180 μm was produced using an air-cooled inflation film forming machine. The tensile strength and odor of the produced film are shown in Table 2. The composition of the monolayer film was the same as that of the inner layer and the outer layer of the barrier multilayer film of Example 1. In addition, LDPE1 having the same composition as the inner layer and outer layer of the barrier multilayer film of Example 1 was directly subjected to an air-cooled inflation film forming machine to produce a single layer film having a thickness of 50 μm. The formability, appearance, film odor and film seal strength of the film are shown in Table 2.

[0075] <Evaluation method> <Evaluation of oxygen barrier properties> The oxygen permeability of the prepared film was measured using OX-TRAN manufactured by MOCON under conditions of 20° C. and relative humidity of 65%, and the oxygen barrier property was evaluated based on the following evaluation criteria. Evaluation Criteria ◎: Oxygen permeability 5.0cc / (m 2 ·day) or less. ○: Oxygen permeability 5.0cc / (m 2 ·day) super 10.0cc / (m 2 ·day) or less. ×: Oxygen permeability 10.0cc / (m2 ·day) Super.

[0076] <Film odor> The odor of the prepared film was evaluated by a panel of three people. The criteria for the odor evaluation were as follows: "◎" if almost no odor was detected, "◯" if the odor was slightly detected but not bothersome, and "×" if the odor was detected and unpleasant.

[0077] <Film formability> When the T-die film could be stably formed without thickness unevenness or when the inflation film bubble could be stably formed, it was marked with "◎". When the T-die film had some thickness unevenness but could be formed or when the inflation film bubble was somewhat unstable, it was marked with "◯". When the T-die film or inflation film was unstable and could not be formed, it was marked with "X".

[0078] <Film appearance> The appearance of the produced film was visually checked to see if it was good. The visual evaluation criteria were as follows: "◎" if the transparency and the state of the lumps were almost the same as when the virgin raw materials were used, "〇" if it was slightly whiter than when the virgin raw materials were used but the lumps were not noticeable, and "×" if it was clearly whiter than when the virgin raw materials were used and the lumps were more noticeable.

[0079] <Heat seal strength> A test piece consisting of two inflation films stacked with their inner surfaces facing each other was heat-sealed by applying temperature and load for a specified time, and the force (N / 15 mm) required to pull the two heat-sealed test pieces apart was taken as the heat-seal strength. Heat seal temperature: 140℃ Heat seal pressure: 0.2MPa Heat sealing time: 1sec Test speed: 500mm / min. - Test piece width: 15mm

[0080] <Film tensile strength> The tensile strength at break (MPa) of the film was measured by punching out a JIS No. 1 tensile dumbbell-shaped test piece (10 mm wide at the central parallel part), stretching it at 23°C with a chuck distance of 40 mm and a tensile speed of 500 mm / min, and measuring the stress at which the test piece broke.

[0081] [Table 1]

[0082] [Table 2]

[0083] <Summary of evaluation results> The multilayer barrier films of Examples 1 to 3 of the present invention had little odor and showed good oxygen gas barrier properties, and when the recycled resin composition was used to form a film again, the film had little odor and showed good formability as well.The multilayer barrier films of Examples 4 to 6 also had little odor and showed good tensile strength, and when the recycled resin composition was used to form a film again, the film had little odor and showed good formability and seal strength as well. However, in Comparative Examples 1 and 2, in which the barrier layer was thinner and thicker than that of the present invention, the performance of the barrier multilayer film was insufficient, and it was difficult to re-form the film. Also, in Comparative Example 4, in which an adhesive was used in the outer and inner layers of a barrier multilayer film, a strong odor was sometimes observed, even though the total amount of adhesive used was less than that of Example 6. [Explanation of symbols]

[0084] 10. Barrier multilayer film 1 Outermost layer (first layer) 2 Innermost layer (second layer) 3. Barrier layer 4 Adhesive layer

Claims

1. A thermoplastic film having a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of a recycled resin composition, The recycled resin composition is a recycled product of a barrier multilayer film having an unstretched barrier layer, a thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; The thermoplastic multilayer barrier film is substantially free of a compatibilizer in the layer constituting the outermost surface thereof.

2. 2. The thermoplastic film for recycling according to claim 1, wherein the barrier multilayer film has an adhesive layer, and the thickness ratio of the adhesive layer in the barrier multilayer film is 5% or more and 30% or less.

3. The thermoplastic film of claim 2 , wherein the adhesive layer comprises maleic anhydride modified polyethylene.

4. The thermoplastic film according to claim 2 or 3, wherein the adhesive layer accounts for 5% or more and 20% or less of the recycled layer.

5. The thermoplastic film of claim 1 or 2, wherein the barrier layer comprises a polyamide or an ethylene-vinyl alcohol copolymer.

6. The thermoplastic film according to claim 1 or 2, wherein the composition ratio of the barrier layer in the recycled layer is 1% or more and 30% or less.

7. The thermoplastic film according to claim 1 or 2, wherein the recycled resin composition is produced by melt-kneading the barrier multilayer film.

8. The thermoplastic film according to claim 1 or 2, wherein the thermoplastic resin is a polyolefin resin.

9. A packaging material using the thermoplastic film according to claim 1 or 2.

10. A method for producing a thermoplastic film having a recycled layer containing 0 to 90 parts by weight of a thermoplastic resin and 10 to 100 parts by weight of a recycled resin composition, The recycled resin composition is a recycled product of a barrier multilayer film having an unstretched barrier layer, a thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; The method for producing a thermoplastic film, wherein the barrier multilayer film is substantially free of a compatibilizer in a layer constituting an outermost surface thereof.

11. A barrier multilayer film for regeneration, having an unstretched barrier layer, to be recycled as a thermoplastic film, comprising: a thickness ratio of the barrier layer in the barrier multilayer film is 6% or more and 32% or less; A barrier multilayer film, wherein the layer constituting the outermost surface of the barrier multilayer film is substantially free of a compatibilizing agent.

Citation Information

Patent Citations

  • BARRIER FILM, MANUFACTURING METHOD THEREOF, AND ARTICLE CONTAINING THE SAME

    JP2017518205A

  • Recyclable laminate, and packaging material and package manufactured through recycling

    JP2020011415A